The Effect of the Different Concentration and Proportion of Mixtures of Actara Insecticide and Ginger Oil in the Mortality Rate of Larvae of Greater Wax Moth, Galleria Mellonella L. - Al-sinjari, Sofyan H. S. (Science Journal of University of Zakho, 2017)
During this study the toxic effect of Actara and ginger oil of Zingiber officinale, individually or in combination, on the 3rd and 5th instar larvae of greater wax moth, Galleria mellonella L. was investigated. The percentages of mortality of 3rd and 5th instars larval stage exposed for Actara, at concentrations of 0.1, 0.15 and 0.2 µl/ larva, after 24 hours exposure were 17.50, 25.00 and 32.50 %, and 10.00, 12.50 and 17.50 respectively. The percentages of mortality of 3rd and 5th instars larval stage exposed to mixture 1:1 of Actara insecticide and ginger oil at concentrations of 0.1, 0.15 and 0.2 µl/ larva were 26.60, 40.00 and 50.00% (for 3rd instar), and 20, 26.60 and 33.30% (for 5th instar) respectively, after exposure period of 24 hours. While the mortality of 3rd and 5th instars larval stage exposed to the mixing ratio 1:2 (Actara insecticide and ginger oil) of the same concentrations and same exposure period mentioned previously, were 36.60, 46.00 and 63.30 % (for 3rd instar), and 26.60, 36.60 and 46.60% (for 5th instar), respectively. Whereas in the mixing ratio 1:3(Actara insecticide and ginger oil) of same concentrations and same exposure period mentioned previously, the mortality (3rd and 5th instars larvae) were 53.30, 63.00 and 90.00 % (for 3rd instar), and 33.30, 46.60 and 63.00% (for 5th instar), respectively. The synergistic ratios for 3rd and 5th instars larval stage exposed to mixtures 1:1, 1:2 and 1:3 (different concentrations of Actara insecticide and ginger oil), were 1.25, 1.6 and 2.4 (for 3rd instar), and 1.88, 3.50 and 4.01 (for 5th instar), respectively, after 24 hours of exposure. This indicates that a combination of different concentrations of the Actara insecticide with ginger oil produced synergistic effect.